Probing redox reactions of immobilized cytochrome c using evanescent wave cavity ring-down spectroscopy in a thin-layer electrochemical cell. - Powell, H; Schnippering, M; Cheung, M; Macpherson, J; Mackenzie, S; Stavros, V; Unwin, P (2010)
We report the use of evanescent wave cavity ring-down spectroscopy (EW-CRDS) to monitor the reduction by ethylenediaminetetraacetic acid iron(II) complex, [FeEDTA](2-), of an adsorbed layer of oxidized cytochrome c immobilized on fused silica. The adsorption of cytochrome c at the silica-water interface was also probed using EW-CRDS and found to be in qualitative agreement with previous studies. The reduction of the adsorbed cytochrome c was achieved by using a strategically positioned electrode to electrogenerate FeEDTA(2-), which diffused to the silica surface and reduced the cytochrome c. The difference in the absorption spectra of the reduced and oxidized forms of cytochrome c at 400 nm allowed the direct monitoring of the electron transfer in real time. Using finite-element modelling, the rate constant of electron transfer (ET) between FeEDTA(2-) and cytochrome c was found to be 4.3(± 0.6) × 10(-9) cm s(-1) equivalent to 2.7(± 0.4) M(-1) s(-1). The latter value is considerably lower than previously reported ET rate constants between cytochrome c and FeEDTA(2-) in solution, which can be attributed to the confinement of the immobilized cytochrome c on the surface and possible effects from molecular crowding. This study highlights the importance of new methods which can be used to study ET at interfaces and opens up the possibility of studying ET to proteins in biologically relevant environments using EW-CRDS.